Computerized Analysis of Digital Photographs for Evaluation of Tooth Movement - Mohammad Hossein Toodehzaeim; Maryam Karandish; Mohammad Nabi Karandish (Tehran University of Medical Sciences, 2015)
Objectives: Various methods have been introduced for evaluation of tooth movement in orthodontics. The challenge is to adopt the most accurate and most beneficial method for patients. This study was designed to introduce analysis of digital photographs with Auto- CAD software as a method to evaluate tooth movement and assess the reliability of this method. Materials and Methods: Eighteen patients were evaluated in this study. Three intraoral digital images from the buccal view were captured from each patient in half an hour inter- val. All the photos were sent to AutoCAD software 2011, calibrated and the distance be- tween canine and molar hooks were measured. The data was analyzed using intraclass cor- relation coefficient. Results: Photographs were found to have high reliability coefficient (P > 0.05). Conclusion: The introduced method is an accurate, efficient and reliable method for eval- uation of tooth movement.